Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Review: 14



Work Step by Step

$\sqrt[3] (\frac{27y^{3}}{z^{12}})=\sqrt[3] (27y^{3})\times\sqrt[3] (\frac{1}{z^{12}})=3y\times\frac{1}{z^{4}}=\frac{3y}{z^{4}}$ We know that $\sqrt[3] (27y^{3})=3y$, because $(3y)^{3}=(3\times3\times3)\times y^{3}=27y^{3}$. We know that $\sqrt (\frac{1}{z^{12}})=\frac{1}{z^{4}}$, because $(\frac{1}{z^{4}})^{3}=(\frac{1}{z^{4\times3}})=\frac{1}{z^{12}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.